Exhibition Reviews. (1st March 2015) - Leoni, Francesca; Moser, Sarah; Çelik, Zeynep; Behiery, Valerie
'Qalam: The art of Beautiful Writing', Birmingham Museums and art Galleries, Birmingham, UK, November 2, 2013–January 26, 2014'How Architects, Experts, Politicians, International Agencies and Citizens Negotiate Modern Planning: Casablanca Chandigarh', Canadian Centre for Architecture, Montreal, November 26, 2013–April 20, 2014'Robertson: Photographer and Engraver in the Ottoman Capital', Koç University Research Center for Anatolian Civilizations, Istanbul, November 27, 2013–February 20, 2014'"The Map is not the Territory": Parallel Paths – Palestinians, Native Americans, Irish', Levantine Center, Los Angeles, May 15–June 22, 2014